Palliative Care in Congenital Syndrome of the Zika Virus Associated with Hospitalization and Emergency Consultation: Palliative Care and Congenital Syndrome of Zika - Aline Maria de Oliveira Rocha; Maria Julia Gonçalves de Mello; Juliane Roberta Dias Torres; Natalia de Oliveira Valença; Alessandra Costa de Azevedo Maia; Nara Vasconcelos Cavalcanti (Journal of Tropical Medicine)
Background. Congenital syndrome of Zika virus (CSZV) is associated with neuromotor and cognitive developmental disorders, limiting the independence and autonomy of affected children and high susceptibility to complications, so palliative care needs to be discussed and applied. Aim. To identify factors associated with emergency visits and hospitalizations of patients with CSZV and clinical interventions performed from the perspective of palliative care. Design. This is a cross-sectional study with bidirectional longitudinal component. Data were collected between May and October 2017 through the review of medical records and interviews with relatives of patients hospitalized. Setting/Participants. The study was developed in a tertiary care hospital involving patients with confirmed CSZV born as of August 2015 and followed up until October 2017. Patients under investigation were excluded. Results. 145 patients were followed up at the specialized outpatient clinic, 92 (63.5%) were consulted at least once in the emergency room, and 49% had already been hospitalized, with the main reason being neurological causes, while 24.1% had never required any emergency visit or hospitalization. No risk factors were associated with the occurrence of consultations or hospitalizations. Such events happened at an early age and were accompanied by a high number of invasive procedures and interventions. An approach in palliative care was only identified in two hospitalized patients. Conclusions. For the patient with known severe malformations caused by congenital infection by the Zika virus with indication of palliative care, this approach could be used in order to allow life without suffering and disproportionate invasive method.